If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -4 = 0 Reorder the terms: -4 + -4x = 0 Solving -4 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -4x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = 0 + 4 -4x = 0 + 4 Combine like terms: 0 + 4 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| 1+.6(q-4)=.4(q+1) | | 0.7x-4.7=0.9 | | 5m+2(mh)=23 | | 7-2r=15 | | 2x-7+3x=53 | | 3x+4x=x+6 | | .40x+.20(130)=.20(128) | | 7k-2=12 | | -3c-12=-5c+c | | 9J+3= | | 7y+3(y-6)=5(y+1)-2 | | 2x+5x=3x | | 4(6-3x)-8(X-24)=-7X+X | | 33+15x=3x-x+4x | | 17+5y+9=3y+5y+9 | | 6x-15+2x=7 | | X-4=x+1 | | 4x+5=2x-15 | | -5t+10=8t-9 | | 4z+2-z=9+2z+9 | | 7.6-5x+5.5=1.6 | | 10+4x+6x=-1 | | -7x-2=40 | | 2b-3=18 | | 3(5-a)-23=21a-4(2+6a) | | X+28=49 | | 4(x-5)=3(x-2) | | 2c+25=100 | | 2.32x+7.41=-4.78x-8.21 | | -44=6x+7x+8 | | 6-(2p+5)=6[(2p-5)-(p-3)] | | 6(5v+2)=-20-2v |